PM2.5-bound PAHs near a typical industrial park: Determining health risks associated with specific industrial sources. (1st June 2023) - Bi, Siqi; Cao, Hongbin; Zhang, Bohan; Dong, Haibo; Gao, Yue; Zhou, Xu; Jiang, Yanxue; Jiang, Wenjuan
Abstract: Source-specific potential health risk was proposed as an effective index for determining priority control sources of PM2.5 -bound polycyclic aromatic hydrocarbons (PAHs) near an industrial park. However, industry-specific emission profiles were limited. In this study, 60 emission source samples from 13 industries and 139 p.m.2.5 samples near an industrial park were collected from 2020 to 2021. The PAH profiles of 12 industrial emission sources were constructed to address the difficulty of source apportionment refined to industrial categories. A diagnostic ratio method and a positive matrix factorization method (PMF) were used to qualitatively and quantitatively determine the emission sources of 16 p.m.2.5 -bound PAHs. The incremental lifetime carcinogenic risk (ILCR) of PAH inhalation exposure for the local population was attributed to sources by a PMF-ILCR model. The results show that the local PAH pollution seriously exceeded (86.3% sampling days) the standard (GB3095-2012). The concentration of PAHs was 33.6 ± 32.6 ng/m 3 and showed a seasonal trend of "heating season > autumn > spring". There were five main sources of PM2.5 -bound PAHs near the industrial park: heavy oil combustion (29.8%), coal and natural gas combustion (28.0%), vehicle emissions (19.9%), steel industry emissions (19.4%) and tar volatilization (2.9%). There is potential carcinogenic risk to both children (3.1 × 10 −6 ) and adults (1.2 × 10 −5 ). The mass contribution of each source to ambient PAHs is not equivalent to its contribution to potential health risk. The risks of PM2.5 -bound PAHs almost all correspond to vehicle emissions (46.3%), heavy oil combustion (25.9%) and steel industrial sources (24.9%). Graphical abstract: Image 1 Highlights: PAH profiles for some typical industrial categories were constructed. More representative potential sources of PM2.5 -bound PAHs were identified. Industry-related sources were refined in PAH source apportionment. A PMF-ILCR model was used to assess the source-specific carcinogenic risks of PAHs. Vehicle emissions corresponded to the highest carcinogenic risk of PAHs.